2019
DOI: 10.1103/physrevapplied.12.034016
|View full text |Cite
|
Sign up to set email alerts
|

Convective Dissolution of Carbon Dioxide in Deep Saline Aquifers: Insights from Engineering a High-Pressure Porous Visual Cell

Abstract: We present the first experiments of dissolution-driven convection of carbon dioxide (CO2) in a confined brine-saturated porous medium at high pressures. We designed a novel Hele-Shaw cell that allows for both visual and quantitative analyses, and address the effects of free-phase CO2 and brine composition on convective dissolution. The visual examination of the gas volume combined with the measurement of pressure, which both evolve with dissolution, enable us to yield insights into the dynamics of convection i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 89 publications
0
22
0
Order By: Relevance
“…Density‐driven convective flow is ubiquitous in natural systems, such as water infiltration into soil (Assouline, 2013), atmospheric movement (Hodges & Thorncroft, 1997) and oceanic currents (Ruddick & Gargett, 2003). Density‐driven convection has an wide application for flow in porous media, including geothermal energy production (Cheng & Minkowycz, 1977), oil separation from sand (Taylor, 2018), and carbon dioxide sequestration (Amooie et al, 2018; Mahmoodpour et al, 2019). It is well identified that when dense fluid sits above less dense fluid due to solute concentration and/or temperature, the system is easy to lose its equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…Density‐driven convective flow is ubiquitous in natural systems, such as water infiltration into soil (Assouline, 2013), atmospheric movement (Hodges & Thorncroft, 1997) and oceanic currents (Ruddick & Gargett, 2003). Density‐driven convection has an wide application for flow in porous media, including geothermal energy production (Cheng & Minkowycz, 1977), oil separation from sand (Taylor, 2018), and carbon dioxide sequestration (Amooie et al, 2018; Mahmoodpour et al, 2019). It is well identified that when dense fluid sits above less dense fluid due to solute concentration and/or temperature, the system is easy to lose its equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…CO 2 dissolution in brine causes density-driven convection, which is a key mechanism for the efficient trapping of CO 2 . CO 2 convective dissolution accelerates the CO 2 mass transfer rate and reduces the risk of leakage, which is favorable for long-term sequestration [ 7 ]. Although there are some CCS pilot projects distributed in different parts of the world, there is still a lack of relevant knowledge concerning convective dissolution in CCS projects.…”
Section: Introductionmentioning
confidence: 99%
“…As the spatial and temporal scales involved make it difficult to analyze these dynamics in situ, the experimental research on convective dissolution at the laboratory scale is receiving more and more attention [ 18 , 19 , 20 ]. Three main types of experimental methods have been used to analyze CO 2 convective dissolution in aqueous solutions: PVT (pressure-volume-temperature) reactor experiments [ 21 , 22 , 23 ], Hele–Shaw cell experiments [ 7 , 16 , 24 , 25 ], and bead pack experiments [ 18 , 19 , 26 , 27 ]. PVT reactor experimental results can be used to easily quantify the total dissolved CO 2 mass and mass transfer rate at high pressures and elevated temperatures; however, they have limited ability to visualize the convective dissolution process.…”
Section: Introductionmentioning
confidence: 99%
“…The small density difference of the CO 2 -brine system that drives the convective mixing process is replicated in these fluids 5,9,10 . More recently, a few studies have attempted to examine convective mixing at conditions that more closely reflect that in the field, particularly by performing experiments using actual CO 2 -brine 11 at high-pressure conditions within a porous medium [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%